Ecological Awareness in the Light of Theory and Practice (an Outline of a Political-Science Model of Ecological Awareness) - Papuziński, Andrzej (Problemy Ekorozwoju, 2006)
The paper aims to show how essential it is that a model of ecological awareness based on political science and used as a concept emphasizing motivation for pro-ecological activities should be devised. In this connection, the author discusses the reasons for differences in the defining of ecological awareness, the range of correct usage of this category, and two theoretical models of ecological awareness: the ethical and the sociological. The analysis was made on the basis of two assumptions. While the first concerns the dependence of each theoretical model on the specifics of the scientific discipline in which it is formed, the other applies to the necessity of possessing analytical capabilities (with a view to creating an active pro-ecological attitude), that allow relations between a description and a norm to be elucidated.